Bio-Inspired Underwater Super Oil-Repellent Coatings for Anti-Oil Pollution - Chen, Yupeng (Langmuir : the ACS journal of surfaces and colloids, 2018)
Underwater superoleophobic surfaces have attracted great attention due to their broad applications such as anti-oil adhesion, oil capture and transportation, and oil/water separation. However, it is often fairly complex and time-consuming, involved in the construction of micro/nanostructures and the regulation of chemical compositions; there is an urgent need to develop new strategies to conquer these problems. Inspired by the strong anchoring capability and easy accessibility of plant polyphenols, we can readily and rapidly fabricate tannic acid (TA) coated copper surfaces with the excellent underwater super oil-repellent property. To achieve the optimal condition for TA modification, the influence of immersion time, TA concentration, and pH value on underwater-oil wettability and adhesion has been systematically explored. Furthermore, the underwater super oil-repellent feature can be widely achieved for different oils and on various metal sheets, suggesting the potential applications for plenty of fields such as anti-oil pollution